Challenges Faced by Consumers in Buying Kitchen Gardening Products through Online Platforms in Ahmedabad, Gujarat, India - Nikita Manubhai Parmar; Shakti Ranjan Panigrahy; Abhishek Pipaliya (Archives of Current Research International, 2025)
Background: Kitchen gardening (also called home or nutrition gardening) is the practice of cultivating fruits, vegetables, herbs, and medicinal plants around one’s home primarily for household consumption, sometimes with surplus sale. Selling kitchen gardening products online also poses challenges, especially in India. Limited digital literacy and payment infrastructure in semi-urban and rural areas mean some consumers remain hesitant about online shopping. Purpose: To address the food diversity and to tackle growing malnutrition issues in the resource crunch environment, Kitchen gardening practices are a notable solution both for the producers and consumers that drive many of the business opportunities; especially ecommerce segments that generate value by minimising intermediaries. Research Methodology and Data Collection: Trust, reliability, inadequate information, poor packaging and delivery delays in the online business ecosystem are a continual problem that needs to be addressed. Looking at it as a prospective issue, the current study has been taken in the Ahmedabad district of Gujarat; more specifically, in its three talukas, viz., Ahmedabad, Daskroi, and Dholka talukas, where 100 kitchen gardening producers were targeted with a structured schedule for understanding factors influencing and constraints faced by them in buying kitchen gardening products. Findings: Consumer assurance emerged as the most dominant motivator, followed by price sensitivity, product reviews, time-saving features, and customer service quality. Finally, the most pressing challenges consumers faced included high delivery charges, poor product quality, and insufficient product descriptions, which impacted both the purchase experience and gardening outcomes. Conclusion: Kitchen gardening is a key source of nutritional diversity and chemical-free food for both rural and urban populations. It is suggested to focus on customer protection, reliability, prices and bundle offers to get a high share of the customer base on e-commerce platforms.